Pembuatan Sistem Informasi Persediaan Barang pada PT Lumasindo Sumber Abadi: Development of Inventory Information System at PT Lumasindo Sumber Abadi - Evi Lestari Pratiwi; Ramadhani Noor Pratama; Inayatul Ulya Ahyati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This community service aims to design and develop an inventory management system at PT Lumasindo Sumber Abadi. The background of this community service is the company's need to improve operational efficiency and data accuracy in managing stock, which was previously done manually and was prone to errors. The system development method used is a structured approach that includes the following stages: needs analysis, system design, implementation, and testing. Data is obtained through direct observation, interviews with relevant stakeholders, and literature studies to ensure that the approach used meets the company's needs. The expected outcome of this community service is to demonstrate that the developed information system can significantly improve the company's operational efficiency. This system simplifies the management of sales and stock items and improves the accuracy and speed of data processing. The implementation of the inventory management information system is expected to provide significant benefits for PT Lumasindo Sumber Abadi in daily operations and can serve as a model for other companies facing similar challenges.